Evoecotoxicology: Environmental Changes and Life Features Development duringthe Evolutionary Process—the Record of the Past at DevelopmentalStages of Living Organisms - Herkovits, Jorge (2006)
For most of evolutionary history, scientific understanding of the environment and life forms is extremely limited. In this commentary I discuss the hypothesis that ontogenetic features of living organisms can be considered biomarkers of coevolution between organisms and physicochemical agents during Earth’s history. I provide a new vision of evolution based on correlations between metabolic features and stage-dependent susceptibility of organisms to physicochemical agents with well-known environmental signatures. Thus, developmental features potentially reflect environmental changes during evolution. From this perspective, early multicellular life forms would have flourished in the anoxic Earth more than 2 billion years ago, which is at least 1.2 billion years in advance of available fossil evidence. The remarkable transition to aerobic metabolism in gastrula-stage embryos potentially reflects evolution toward tridermic organisms by 2 billion years ago. Noteworthy changes in embryonic resistance to physicochemical agents at different developmental stages that can be observed in living organisms potentially reflect the influence of environmental stress conditions during different periods of evolutionary history. Evoecotoxicology, as a multidisciplinary and transdisciplinary approach, can enhance our understanding of evolution, including the phylogenetic significance of differences in susceptibility/resistance to physicochemical agents in different organisms.